2020
DOI: 10.3150/20-bej1193
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of persistence diagrams for topological crackle

Abstract: In this paper we study the persistent homology associated with topological crackle generated by distributions with an unbounded support. Persistent homology is a topological and algebraic structure that tracks the creation and destruction of homological cycles (generalizations of loops or holes) in different dimensions. Topological crackle is a term that refers to homological cycles generated by "noisy" samples where the support is unbounded. We aim to establish weak convergence results for persistence diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A different approach was taken in [103], where persistence diagrams were studied from the point of view of set-topology. In that case it was shown that each persistence diagram can be roughly split into three different areas.…”
Section: Limit Theoremsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different approach was taken in [103], where persistence diagrams were studied from the point of view of set-topology. In that case it was shown that each persistence diagram can be roughly split into three different areas.…”
Section: Limit Theoremsmentioning
confidence: 99%
“…• Functional limit theorems: One can examine functionals such as the Betti numbers and the Euler characteristic in a dynamic setting, and seek a limit in the form of a stochastic (Gaussian) process. In [103,108], geometric complexes were studied, and the dynamics was the growing connectivity radius in the complex. The results show that the limiting process is indeed Gaussian.…”
Section: Other Directionsmentioning
confidence: 99%
“…After the pioneering paper of [1], the layered structure in Figure 2 has been intensively studied via the behavior of various topological invariants [16,14,15,17,22]. In particular, from the viewpoints of (1.4), we have in an asymptotic sense,…”
Section: Introductionmentioning
confidence: 99%
“…As expected from Figure 2, it is not surprising that the stochastic features of (1.4) drastically vary, depending on how rapidly R n diverges. Among many of the related studies [16,14,15,17,22], the all consist of k + 2 points). If R n diverges even more slowly, so that R n = R d,n = (Cn) 1/α , then U (t) becomes highly connected in the area close to a boundary of a weak core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation